Artificial Ageing of Aluminum Alloys. Statistical Studies of Results - Smeadă, Mihaela; Stoicănescu, Maria; Radomir, Irinel; Geamăn, Lucica (Elsevier BV, 2012)
The materials used in aircraft industry beside the light specific weight, must respond to some specific requirements for creation of new materials and also the improvement of the material properties used in the present.In modem aircraft construction there are many casting pieces, such as props, fittings, flanges, handles, crossing tight bodies, etc. Casting alloys used are based on aluminum alloys, magnesium-lithium alloys, vanadium-aluminum alloys, titanium alloys, etc.Aluminum alloy, the ones which are light and have good physical and mechanical properties, are part of common materials used in producing some components found in aircraft technology. In terms of experimentally point of view, the application of different artificial ageing heat treatments leads to an improvement of the mechanical properties compared with the results registered by natural aging.Experimental researches made on samples of ATSi6Cu4Mn aluminum alloy artificially aged by unconventional heat treatments highlights the obtaining of improved mechanical properties, the results representing a very useful database under the terms of the data being properly recorded.The verification by a statistical test of the experimental data registration in a normal distribution represents in this case the necessary condition for the validation of the results.
Keywords: aluminum alloyheat treatmentmechanical propertiesmathematical statistic